PENGARUH KESIAPAN KERJA MAN POWER TERHADAP KETEPATAN WAKTU PELAKSANAAN PROYEK KONSTRUKSI GEDUNG DI KOTA MAKASSAR - Kalangi, Hendry Tanoto; Tecoalu, Gladys Gabriella (Jurnal Media Teknik Sipil, 2024)
Leadership is one of the important aspects in project control. Cost, quality and time can be controlled by a series of procedures carried out by project personnel on project resources. The study further studies the Hershey-Blanchard leadership theory as a reference in the interaction between leaders in this case staff or project managers with individuals they lead in this case labor (craftsmen) and their influence on the timeliness of project implementation in Makassar City. The method used in this study is a quantitative method with the Wilcoxon Hypothesis and Spearman Correlation Test. The results obtained from the hypothesis test are that there are differences between the less confident group (Group 1) and the less competent but confident group (Group 2) and between the competent but unmotivated group (Group 3) and the highly competent group on project delays (Group 4) on building project delays in Makassar City. The results of the hypothesis test also showed no difference between the less competent but confident group (Group 2) and the competent but unmotivated group (Group 3) on project delays. The correlation test showed that for groups 1, 2, 3, 4 on project delays were 0.20922, 0.13075, -0.34738, -0.13911, respectively, which means that if Groups 1 and 2 were given a professional approach, it might be one of the causes of delays in the building project in Makassar City and if Groups 3 and 4 were given a professional approach, it would not be one of the causes of project delays in Makassar City.